The Development and Psychometric Assessment of a Coping Inventory for Intimate Partner Violence Among Abused Iranian Women - Taherkhani, Sakineh (Journal of interpersonal violence, 2022)
Helping abused Iranian women better cope with intimate partner violence (IPV) requires measuring their coping strategies. The review of literature on the subject showed that there is no context-based instrument for measuring coping with IPV among abused Iranian women. The present study was thus conducted to develop and perform the psychometric assessment of a coping inventory for intimate partner violence (CIIPV) in abused Iranian women.In this methodological study, two consecutive studies were carried out for the development and psychometric assessment of CIIPV. In the first study, the inventory items were designed based on the results of a previous qualitative study that was conducted to identify the coping strategies used for IPV among abused Iranian women. In the second study, the inventory?s validity and reliability were examined. The face validity, content validity, construct validity, and convergent validity of the inventory were also evaluated. Moreover, to assess the reliability of the inventory, its internal consistency was estimated using Cronbach?s alpha coefficient.A total of 58 items were designed in the first study and then psychometrically assessed. The final version of the inventory comprised 29 items and 6 factors, including negotiation, instrumental action, help-seeking, positive cognitive restructuring, spiritual support-seeking, and distraction. The content validity index of the entire inventory was 1. The extracted factors explained 75.44% of the variance. The convergent validity of the CIIPV was confirmed with a medium positive relationship between the conceptually similar subscales in the two instruments CIIPV and the Ways of Coping Questionnaire. Furthermore, the Cronbach?s alpha coefficient of the entire inventory was 0.86, indicating its suitable reliability. Given the results, the CIIPV is a valid and reliable domain-specific tool to measure the coping strategies used for IPV among abused Iranian women.